Influence of systemic copper toxicity on early development and metamorphosis in Xenopus laevis. Issue 3 (19th September 2022) - Fort, Douglas J.; Todhunter, Kevin J.; Wolf, Jeffrey C.; Long, Kevin; Poland, Craig A.; McGrath, Micheal; Baken, Stijn; Mackie, Carol
Abstract: The primary objective of the present study was to examine the influence of early systemic toxicity resulting from copper (Cu) exposure on metamorphic processes in Xenopus laevis . A 28‐day exposure study with copper, initiated at developmental stage 10, was performed using test concentrations of 3.0, 9.0, 27.2, 82.5, and 250 μg Cu/L. The primary endpoints included mortality, developmental stage, embryo‐larval malformation, behavioral effects, hindlimb length (HLL), growth (snout‐vent length [SVL] and wet body weight), and histopathology. The 28‐day LC50 value with 95% confidence intervals was 61.2 (51.4–72.9) μg Cu/L with 250 μg Cu/L resulting in complete lethality. Developmental arrest in the 82.5 and delay in the 27.2 μg Cu/L treatments was observed as early as study day 10 continuing throughout the remainder of exposure. SVL‐normalized HLL, body weight, and SVL in the 27.2 and 82.5 μg Cu/L treatments were significantly decreased relative to control. At 82.5 μg Cu/L, and thyroid gland size was markedly reduced when compared with controls consistent with the stage of developmental and growth arrest. Concentration‐dependent findings in the intestine, liver, gills, eyes, and pharyngeal mucosa were consistent with non‐endocrine systemic toxicity. These were prevalent in the 9.0 and 27.2 μg Cu/L treatment groups but were minimally evident or absent in the 82.5 μg/L group, which was attributed to developmental arrest. In conclusion, developmental delay in larvae exposed to 27.2 and 82.5 μg Cu/L was the result of systemic toxicity occurring in early development prior hypothalomo‐pituitary‐thyroid axis (HPT)‐driven metamorphosis and was not indicative of endocrine disruption. Abstract : The primary objective of the present study was to examine the influence of early systemic toxicity resulting from copper (Cu) exposure on metamorphic processes in Xenopus laevis . A 28‐day exposure study with copper, initiated at developmental stage 10, was performed using test concentrations of 3.0, 9.0, 27.2, 82.5, and 250 μg Cu/L. Developmental delay in larvae exposed to 27.2 and 82.5 μg Cu/L was the result of systemic toxicity occurring in early development prior hypothalomo‐pituitary‐thyroid axis (HPT)‐driven metamorphosis and was not indicative of endocrine disruption.